Double Lumen Tubes: Usage and Performance by Frequent and Infrequent Users. (1st November 2011) - Jha, Sachin; Ehrenfeld, Jesse M.
Abstract : Double lumen tubes (DLT) are commonly used to achieve lung isolation (LI). Not all anesthesiologists are frequent DLT users. Our thoracic surgical service is covered by sub-specialty anesthesiologists who are frequent DLT users. Thus, we are in a position to evaluate the performance of infrequent DLT users relative to frequent DLT users. Using statistical methods, we examined the incidence, duration and severity of hypoxia, hypercapnea and high airway pressures for patients receiving LI via DLTs placed by infrequent versus frequent users. The incidence of low SpO2, high EtCO2, or high PIP was not different between frequent and infrequent DLT users. However, when these events do occur, they are more severe (elevated EtCO2 duration, lower SpO2, higher EtCO2, higher airway pressure) among infrequent than frequent DLT users. The practical significance of these differences, which are small, is unproven. However, when episodes of hypercapnea do occur, they last much longer among infrequent than frequent DLT users.